Self-disclosed oral hygiene habits from students of Bahria University Medical and Dental College, Karachi campus - Ali, Rabiya; Nadia Khalid; Fareeha; Shireen Jawed; Naila Masood; Fatima Syed (Journal of University Medical & Dental College, 2021)
BACKGROUND & OBJECTIVE: Dental hygiene reflects the overall health and impacts the quality of life. The present study was designed to assess knowledge, attitude, and practices regarding oral hygiene among medical and dental undergraduate students and to compare the oral hygiene habits among male and female students METHODOLOGY: A cross-sectional study was conducted among medical and dental students of Bahria University Medical and Dental College, Karachi (BUMDC) from December 2018 to January 2019. Ethical approval was taken from the ERC committee of Bahria University Medical and Dental College (ERC/2/2018). Students (n= 332) of MBBS and BDS from first to final year were enrolled by non-probability convenience sampling technique. A self-structured questionnaire was used to obtain data. Percentages were determined for each response. The Chi-Square test was used to check the association of oral hygiene outcomes with respect to gender. RESULTS: The study comprised 332 male and female students, out of which 189 (56.9%) were dental and 143(43.1%) were medical. The majority of students (71.4%) were female. The mean age of participants was 20.8± 1.3 years, 44.6% used toothbrushes, 33.7% used toothbrush and floss, and 21.4% used toothbrush and miswak, 61.4% of respondents have brushed their teeth twice a day, 5.1% of respondents were reported bad smell from their teeth, 58.1% were complaining sore jaws. Dental hygiene was significantly associated with gender (p≤ 0.05). Females have better practices and a positive attitude toward oral hygiene. CONCLUSION: Female students had better oral hygiene knowledge and practices with more positive attitude as compared to male counterparts.